Agricultural land-use changes in modern subarctic Europe: adaptations in the Sámi village of Máze, Sápmi (Norway) - Müller-Wille, Ludger; Thannheiser, Dietbert (ERDKUNDE, 2003)
The article discusses the environmental and human factors in the changes of agricultural land-use patterns and practices in a small Sámi river settlement, Máze (Norway) between 1960 and 2000. Aspects of socio-economic changes and developments are discussed. First, the environmental conditions in the European subarctic are outlined, after which the historical emergence of an economically mixed community with reliance on locally based reindeer herding and introduced agricultural hay-dairy economy is analysed. The research method to study the development of Máze land-use relied on intensive large-small mapping surveys between 1964 and 2000 and available statistics on local conditions. The Máze riverine settlement area is presented in its changing demography, human occupancy (housing, cabins, facilities, institutions and infrastructure), and finally farm homesteads and their land-use and production. Two sample years, 1964 and 2000, are compared and changes are related to human factors identifying the intensity of human environmental interactions in a sensitive subarctic ecosystem at the northern fringe of the ecumene.